The Rise and Fall of Regional Industries: The Roles of Inter-Industry - Khairul Rizal (Jurnal Perencanaan Pembangunan: The Indonesian Journal of Development Planning, 2019)
This paper addresses one of the lasting issues in regional development: how regions manage to develop new industries while others fail to do so. It focuses on regional knowledge that is arguably reflected by industry structures. Using inter-industry relatedness measure as a tool to analyze the evolution of industries at the province level, this study finds that industries that are close to a province’ portfolio have a higher probability to emerge and thrive in that province, whereas industries that are less related to its provinces’ portfolio tend to decline and exit. Therefore, regional industrial policies should focus on potential industries that are rather close to the provinces’ portfolio.